Donne's Augustine Renaissance cultures of interpretation - Ettenhuber, Katrin (Oxford : Oxford University Press, 2011)
This is a comprehensive re-examination of John Donne, through his response to the most iconic religious figure in Western theology, Saint Augustine of Hippo. This book enriches our understanding of the reading and writing culture of Renaissance England, and of the religious debates in the decades leading up to the Civil War.
Description based on print version record.
Includes bibliographical references and index.
Keywords: Donne, John, -- 1572-1631 -- Knowledge -- Theology; Donne, John, -- 1572-1631 -- Books and reading; Augustine, -- Saint, Bishop of Hippo -- Influence; Augustine, -- Saint, Bishop of Hippo -- Appreciation -- Great Britain -- History -- 17th century; Theology -- History -- 17th century